The NOMS Framework: Approach to the Treatment of Spinal Metastatic Tumors. (24th May 2013) - Laufer, Ilya; Rubin, David G.; Lis, Eric; Cox, Brett W.; Stubblefield, Michael D.; Yamada, Yoshiya; Bilsky, Mark H.
Abstract : Background: Spinal metastases frequently arise in patients with cancer. Modern oncology provides numerous treatment options that include effective systemic, radiation, and surgical options. We delineate and provide the evidence for the neurologic, oncologic, mechanical, and systemic (NOMS) decision framework, which is used at Memorial Sloan‐Kettering Cancer Center to determine the optimal therapy for patients with spine metastases. Methods: We provide a literature review of the integral publications that serve as the basis for the NOMS framework and report the results of systematic implementation of the NOMS‐guided treatment. Results: The NOMS decision framework consists of the neurologic, oncologic, mechanical, and systemic considerations and incorporates the use of conventional external beam radiation, spinal stereotactic radiosurgery, and minimally invasive and open surgical interventions. Review of radiation oncology and surgical literature that examine the outcomes of treatment of spinal metastatic tumors provides support for the NOMS decision framework. Application of the NOMS paradigm integrates multimodality therapy to optimize local tumor control, pain relief, and restoration or preservation of neurologic function and minimizes morbidity in this often systemically ill patient population. Conclusion: NOMS paradigm provides a decision framework that incorporates sentinel decision points in the treatment of spinal metastases. Consideration of the tumor sensitivity to radiation in conjunction with the extent of epidural extension allows determination of the optimal radiation treatment and the need for surgical decompression. Mechanical stability of the spine and the systemic disease considerations further help determine the need and the feasibility of surgical intervention. Abstract : Spinal metastases frequently arise in patients with cancer. This article describes the neurologic, oncologic, mechanical, and systemic decision framework used at Memorial Sloan‐Kettering Cancer Center to determine the optimal therapy for patients with spinal metastases. Abstract : 摘要 背景 . 癌症患者经常会发生肿瘤脊柱转移。现代肿瘤学提供了众多治疗方案，包括有效的系统治疗、放射治疗和手术治疗。我们描述并提供了解释神经病变学、肿瘤学、机械力学、以及系统[（neurologic，oncologic，mechanical and systemic），NOMS]决策框架的证据，该框架在斯隆‐凯特琳纪念癌症中心用于制定脊柱转移瘤患者的最佳治疗方案。 方法 . 我们对以NOMS框架为基础的主要出版文献进行了文献综述，报告系统实施NOMS指导治疗的结果。 结果 . NOMS决策框架包括对神经病变学、肿瘤学、机械力学以及系统原因的考量，综合应用常规外照射治疗、脊髓立体定向放射外科治疗、微创及开放性手术治疗。旨在调查脊柱转移瘤治疗结果的放射肿瘤学和外科学文献的综述为NOMS决策框架提供了支持。NOMS范例应用时综合多学科治疗以优化局部肿瘤控制、疼痛缓解，恢复或保留神经功能，并将此类容易系统性患病的患者人群的发病率降至最低。 结论 . NOMS范例提供一种决策框架，该框架可汇总脊柱转移瘤治疗中的前哨决策点。针对肿瘤对放射治疗的敏感性结合肿瘤硬膜外侵犯程度的考量，可确定最佳放射治疗方案并符合外科减压手术的需求。针对脊柱的机械稳定性和系统性疾病的考虑更进一步有助于确定外科手术治疗的需求及其可行性。 The Oncologist 2013;18:744–751